(untitled) (Carte Romanze, 2023)
The essay analyzes comparatively the milagro XXI of the collection of Gonzalo de Berceo, De cómmo un abadessa fue preñada, and its source, the miraculum De abbatissa quam beata Maria ad infamia partus et pondere liberavit. The milagro that sees the pregnant superior as human protagonist is a valid test bench to highlight the reworking processes put in place by the Riojano poet: from the rewriting of the prologue and the epilogue of the story to the “dramatization” of its salient scenes, from the accentuation of the typological filigree underlying the narration to the highlighting of the miraculous intervention of Mary and of the exemplary nature of its beneficiary.